THE IMPLEMETATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) TO SOCIAL WELFARE (A Case Study at PT Petrokimia Gresik) - NINDYA PRISANTI KARTIKARINI; Eko Ganis Sukoharsono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
In the current era, increasing the demands of balancing the relationship between the natural, social and economic is along with economic development and the needs of the community. The company is required to understand the principles and implementation of Corporate Social Responsibility (CSR), which the company must provide an active contribution and sensitivity to the environment in the surrounding areas, including human beings who live in that community. This study used a qualitative method for exploring phenomenon of the study, in this case the main phenomenon is CSR of PT. Petrokimia Gresik (PT.PKG). Company that becomes the object of this research is PT. PKG, which is engaged in the field of fertilizers and chemicals. The purpose of this study was to determine the application of CSR to the welfare of society and knowing the results of CSR programs implemented for the welfare of society. This study used data collection techniques are observation, in-depth interviews, documentation, and References review. The results obtained show that, first PT. Petrokimia Gresik has two programs in which Partnership Program and Community Development which is supported by two divisions, namely the Bureau of CSR and PR. Both of these divisions collaborate in achieving the target of CSR is the harmonious relationship builds the economy and the mutualism symbiosis. Secondly, implementation CSR at PT. Petrokimia Gresik in accordance with the principles of CSR and regulations that SOE Ministry Decree number PER-05 / MBU / 2007 dated 27th April, 2007 on the Partnership Program and Community Development Enterprises. Program implemented by the company accepted by the public was supported by the achievement of the results of the satisfaction survey and the lack of friction between the company and the community. Key words : Corporate Social Responsibility, CSR, BUMN, Social Welfare, PT. Petrokimia Gresik